Skin Deep: Alienation in Under the Skin1. Issue 1 (1st January 2015) - Vint, Sherryl
Abstract : This paper reads Jonathan Glazer's Under the Skin as a meditation on how sf represents and responds to difference, particularly issues of ethnic difference. It argues that the film avoids the easy platitude that we are "all the same under the skin" and confronts us instead with the much more challenging prospect of creating empathy across irreconcilable difference. The film explores this prospect largely through its alienating soundscape and innovative use of camera angles, which enable the viewer to experience the world filmed from the alien's point of view, but it does not anthropomorphize the alien to convey this effect. Although Under the Skin ends on a pessimistic note with the violent and fearful destruction of difference, more hopeful visions are offered in John Akomfrah's films Last Angel of History and The Nine Muses .